Optimizing Building Operations with IoT-Enabled Energy Monitoring System - Bhatta, Ashish; Manandhar, Aniket; Chhetri, Bhupendra Bimal; Gachhadhar, Anand; Chapagain, Kamal (Journal of Science and Technology, 2024)
Over the past years, global electricity consumption has surged significantly, highlighting the critical need for effective energy management strategies. These strategies are essential for conserving resources, reducing costs, and promoting sustainable energy use. Buildings alone account for approximately 60% of global energy consumption. Optimally utilizing current technologies can potentially reduce this consumption by 30 to 80%. Collecting extensive building energy consumption data enables the application of data-driven approaches, such as statistical and machine learning techniques, over traditional physics-based methods. An energy management system (EMS) automates data collection and visualization, aiding users in monitoring, analyzing, and managing energy resources. Historical data can be leveraged to develop strategies for optimized energy use, identifying peak and off-peak usage, thereby reducing costs. Commercially available building management solutions are often costly for small and medium-sized buildings, IoT technologies offer a cost-effective alternative. IoT systems connect devices and appliances to a network, facilitating seamless communication and data exchange. Essential components include sensors, actuators, data processing units, and communication networks. Various IoT architectures aim to enhance communication, scalability, security, and efficiency. This paper reviews key literature on IoT-based energy management systems, highlighting research gaps, system architectures, communication standards, real-world implementations. Based on this review a suitable system was developed at Kathmandu University, and the data obtained from the system is analyzed to highlight the critical need for effective energy management strategies.